1999
DOI: 10.1080/00049189993693
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphology of the Sub-Antarctic Australian Territory of Heard Island-McDonald Island

Abstract: The geomorphology of Heard Island± McDonald Island is primarily the product of close interplay between volcanism, glaciation, and vigorous marine processes in a stormy sub-Antarctic environment. The dominant landform is the strato-volcano Big Ben (2745 m), which is the highest mountain on Australian territory outside Antarctica. Other volcanic landforms include scoria cones, domes, open vertical volcanic conduits, lava ¯ows and lava tubes. Volcanic activity is ongoing from the summit of Big Ben, and from Samar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Glaciers at Kerguelen in the Southern Indian Ocean (Frenot et al, 1993; and in southern Patagonia have shown to be shrinking and retreating at accelerated rates (Aniya et al, 1997;Aniya, 1999;Rignot et al, 2003;Rivera & Casassa, 2004). Likewise, rapid glacier recession over the last decades, reflecting temperature rise since the 1950s and 1960s has been found in several locations, including Heard Island (Allison & Keage, 1986;Kiernan & McConnell, 1999;Budd, 2000), and the South Shetland Islands (Braun et al, 2001;Simões et al, 2004).…”
Section: Figure 15 -Total Change In Glacier Length For 103 Marine-tementioning
confidence: 97%
“…Glaciers at Kerguelen in the Southern Indian Ocean (Frenot et al, 1993; and in southern Patagonia have shown to be shrinking and retreating at accelerated rates (Aniya et al, 1997;Aniya, 1999;Rignot et al, 2003;Rivera & Casassa, 2004). Likewise, rapid glacier recession over the last decades, reflecting temperature rise since the 1950s and 1960s has been found in several locations, including Heard Island (Allison & Keage, 1986;Kiernan & McConnell, 1999;Budd, 2000), and the South Shetland Islands (Braun et al, 2001;Simões et al, 2004).…”
Section: Figure 15 -Total Change In Glacier Length For 103 Marine-tementioning
confidence: 97%
“…Hall, 1983a,b;Heilbronn and Walton, 1984a;Löffler et al, 1983;Löffler, 1984;Holness and Boelhouwers, 1998;Kiernan and McConnell, 1999;Holness, 2001a). However, as few process observations and almost no experimental data are available, much of the interpretation of the processes active in the region remains speculative.…”
Section: Introductionmentioning
confidence: 99%
“…Small sand beaches can be found in other protected north-facing sites (Hall and Denton, 2000), but are rare on the mainland. More extensive sand beaches are present on the sub-Antarctic islands, where the subaerial and glacial environment delivers large volumes of sand and gravel to the coasts of South Georgia (Figure 16(c) and 16 (d)) (Gordon and Hansom, 1986), Heard Island (Kiernan and McConnell, 1999), and the nearby Îles Kerguelen (Hansom and Gordon, 1998). Unlike the Arctic coast, where glacial tills and moraine are found in association with extensive deposits of fluviatile sands and gravels, a very different situation occurs on the Antarctic continent.…”
Section: Antarctic Coastal Geomorphologymentioning
confidence: 99%